IMPLEMENTASI MANAJEMEN BERBASIS SEKOLAH (MBS) DALAM PENDIDIKAN ISLAM DI ERA SOCIETY 5.0 : (Studi Multi Kasus di MA Al Hikmah, MA Darussalam, MA Nurul Falah ) - Riza Zainuddin, Mohammad (LPPM STAI Muhammadiyah Probolinggo, 2025)
This study aims to describe the implementation of School-Based Management (SBM) in Madrasah Aliyah in Tulungagung Regency in the era of Society 5.0, identify its supporting and inhibiting factors, and formulate a strategy for integrating Islamic values with technological innovation. Background: Society 5.0 demands that Islamic educational institutions be able to integrate technology with human and Islamic values. SBM, with the principles of autonomy, participation, and accountability, is a strategic approach to improve the quality of education. However, differences in geographical conditions, resources, and organizational culture affect the form of its implementation. Methods: The study used a qualitative approach of multi-case study on three Aliyah Madrasah with different characteristics. Data were collected through in-depth interviews, participatory observations, and documentation studies, then analyzed with Miles, Huberman, and Saldaña's interactive models to find patterns within and between cases. Results: All madrasas apply the principles of MBS, but the level of integration of technology and leadership models varies. MA Al-Hikmah implements community-based management with a focus on basic digital literacy, MA Darussalam adopts distributed leadership with the use of the Learning Management System, and MA Nurul Falah develops transformational leadership based on cutting-edge technological innovations. Supporting factors include visionary leadership, multistakeholder collaboration, and Islamic digital literacy training, while barriers include infrastructure limitations, resistance to change, and technology skills gaps. Conclusion: The success of MBS in the Society 5.0 era is influenced by the suitability of leadership vision, resource capacity, and organizational culture. The resulting value-based MBS model can be adapted by other madrasas to manage educational transformation that is in line with technological developments and Islamic principles.